STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBELAJARAN UNTUK SISWA TUNAGRAHITA DI SLB CG-YPPCG BINA SEJAHTERA SURAKARTA - Sekar Lupita Galih Kinanti; M Mujibburohman; Yetty Faridatul Ulfah (Institut Islam Mamba'ul 'Ulum Surakarta, 2022)
The focus of this research is on the strategy of Islamic Religious Education teachers in learning for mentally retarded children at SLB CG-YPPCG Bina Sejahtera Surakarta. This study aims to describe the strategies and methods used by teachers in learning. This type of research is a qualitative descriptive study with the subject of research being Islamic religious education teachers. In collecting data, the author uses data collection techniques in the form of observation, interviews and documentation. The data obtained were analyzed using Miles and Huberman's analytical model through three stages, namely: data reduction, data presentation and conclusion drawing. The results of this study indicate that in the learning process, teachers use individual approaches, expository strategies and Contextual Teaching Learning (CTL). The method used by the teacher is the lecture method, question and answer, repetition and demonstration.